16 α Hydroxy-(-)-kauran-19-oic Acid: An Antibacterial Diterpene from Sweet Apple (Annona squamosa L., Annonaceae) - Wiart, Christophe; Au, Ta Siang; Mohd, Yusof; Hassan, Hamimah; Sulaiman, Mazdida (Asian Network for Scientific Information, 2005)
The methanolic extract of sweet apple (Annona squamosa L.) showed a good antibacterial activity against both ATCC and clinical strains of Staphylococcus aureus and Streptococcus pneumoniae. 16 Î± Hydroxy-(-)-kauran-19-oic acid, was identified as the compound responsible for the antibacterial activity of this plant.